THE ESSENCE AND PURPOSE OF FOREIGN LANGUAGE LESSONS - Ibragimova Muharram Isakovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The field goals of foreign language classes are to develop students' ability to read, speak, speak and translate the necessary languages, to acquire knowledge of history and culture, to prepare for work in knowledge and diplomacy. These courses have an important tourism in global communication, knowledge and management, students in a wide field. Foreign language classes have a multifaceted impact on individuals, from practical and professional benefits to personal growth and global understanding. Learning foreign languages can be a life-enriching journey in many ways.